Community empowerment through the eco-mosque program at the Ali Bin Abi Tholib Mosque Sorong - Budi Santoso; Jaharudin Jaharudin; Ainul Alim Rahman; Mukhlas Triono (Journal of Community Service and Empowerment, 2025)
The Ali Bin Abi Thalib Mosque is a mosque that stands as a form of awareness of the Muhammadiyah organization in empowering the community. The primary problem lies in the environmentally unfriendly practices of its non-formal educational institutions. to enhance the partners' skills in rainwater harvesting and waste management so that the mosque has an environmentally friendly nuance. Participants are 20 young mosque guards. The Implementation program includes strengthening character education and environmental care movements and rainwater management for mosque guards and teenagers. These community service activities include: preparation, implementation, application of science and technology, and evaluation. This community service resulted in an increased sense of environmental responsibility among the mosque caretakers and teenagers.